Women and leprosy: interferences and experiences - Marcela Gonçalves; Karen da Silva Santos; Simone Santana da Silva; Thalita Caroline Cardoso Marcussi; Kisa Valladão Carvalho; Cinira Magali Fortuna
Objective: to know the interferences of leprosy in women's lives and how they reinvent themselves in coping with the disease. Method: a descriptive study with a qualitative approach. The theoretical-methodological framework adopts an approximation to the cartographic method and some concepts of schizoanalysis, which were used to analyze the data. The tools used to produce the data were the interview and the logbook. The interviews were conducted from July to November 2019, at the participants' homes. Results: the group consisted of nine women. To display the data, we were inspired by Deleuze's ideas about difference and repetition. The results were organized in three thematic axes that address the lives of these women affected by leprosy, which accompany concerns, anxieties and worries about the effects of the disease. The transformations in the female body, the financial maintenance itself due to the comorbidities caused by leprosy and its difficulties in guaranteeing rights are elements strongly pointed out by women. Conclusion: there is overlap and interference of the female condition in a patriarchal society that still accompanies it. We bet on the strength of becoming-a-woman and the need to consider them in their singularities and in their context for producing care permeated by meetings of the affirmation of the power of life.